2019
DOI: 10.1039/c9ra00884e
|View full text |Cite
|
Sign up to set email alerts
|

Sacrificial carbonaceous coating over alumina supported Ni–MoS2 catalyst for hydrodesulfurization

Abstract: Sacrificial carbon coating over NiMo/Al2O3 catalyst effectively tailor the interaction between the active phase and support, which result in more easily reducible active components and enhanced HDS performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…However, coating of the alumina support with the sacrificial carbon layer obtained from the carbonization of polydopamine could promote the reduction and degree of sulfidation of the loaded phase. The HDS catalysts were prepared by loading Ni and Mo on the alumina-PDA supports via the incipient wetness impregnation method, followed by drying at 120 • C and calcinations in flowing air at 500 • C for 2 h. It was observed that at 300 • C, 2 MPa hydrogen pressure, and liquid hourly space velocity of 12 h −1 , the percentage of HDS conversion and the yield of biphenyl increased with increase in the polydopamine concentration and achieved a maximum at an optimum value of the dopamine coating [94]. Studies on cobalt (Co)-molybdenum sulfide (MoS) catalysts on polydopamine-coated alumina supports indicate an increase in the catalytic activity in the hydrogenation of toluene and the hydrodesulfurization of gas oil feed attributed to the increase of accessibility of the active sites due to reduced MoS 2 aggregation and a decrease in metal-support interactions due to the carbonaceous intermediate layer [53].…”
Section: Biopolymer Coating On a Catalystmentioning
confidence: 99%
“…However, coating of the alumina support with the sacrificial carbon layer obtained from the carbonization of polydopamine could promote the reduction and degree of sulfidation of the loaded phase. The HDS catalysts were prepared by loading Ni and Mo on the alumina-PDA supports via the incipient wetness impregnation method, followed by drying at 120 • C and calcinations in flowing air at 500 • C for 2 h. It was observed that at 300 • C, 2 MPa hydrogen pressure, and liquid hourly space velocity of 12 h −1 , the percentage of HDS conversion and the yield of biphenyl increased with increase in the polydopamine concentration and achieved a maximum at an optimum value of the dopamine coating [94]. Studies on cobalt (Co)-molybdenum sulfide (MoS) catalysts on polydopamine-coated alumina supports indicate an increase in the catalytic activity in the hydrogenation of toluene and the hydrodesulfurization of gas oil feed attributed to the increase of accessibility of the active sites due to reduced MoS 2 aggregation and a decrease in metal-support interactions due to the carbonaceous intermediate layer [53].…”
Section: Biopolymer Coating On a Catalystmentioning
confidence: 99%
“…[86] As another series of effective transferring printing methods without stamps [87,88] to realize interface delamination has attracted great attentions, due to its simple and gentle processing. [89] This kind of methods usually using sacrificial layer (materials including polyvinyl alcohol (PVA), [69] polymethyl methacrylate (PMMA), [90] polyvinyl chloride (PVC), [91] and polydopamine (PDA) [92] ) between the donor substrate and electronics, which can be removed under specific liquid [34,89] like water and other media like laser. [93] And, a typical transfer printing process using water-soluble PVA as the sacrificial layer is illustrated in Figure 4a.…”
Section: Stamp-free Transfer Printing Assisted With Liquid or Lasermentioning
confidence: 99%
“…It has been reported in the literature that the rational design of the support may improve the performance of hydrotreating catalyst by tuning the sulfide component composition, morphology, and dispersion. Due to this, recently, to improve hydrotreating catalysts, approaches based on the use of composite supports consisting of alumina and materials characterized by other acid–base (TiO 2 , , SiO 2 , MCM-41, MgO, , TiO 2 –MgO ) or neutral (various carbon material ) properties were proposed. In this regard, much attention has been paid to developing composite supports based on alumina and various carbon materials primarily because each has advantages when used as a support for hydrotreating catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…This approach will also make it possible to modify the alumina surface with different granule shapes and sizes. Various molecules are presented in the literature as precursors to the carbon coating of supports for hydrotreating catalysts, for example, monocarboxylic acids (acetic acid, formic acid, 1-propionic acid, 1-butyric acid), 1,10-phenanthroline, , polydopamine, isopropanol and glycerol, , phytic acid and/or urea . However, the potential for commercial use of these sources to produce carbon coated alumina supports by impregnation with subsequent pyrolysis is questionable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation